Use of touch-down polymerase chain reaction to enhance the sensitivity of Mycobacterium bovis detection - Zumarraga, Martin Jose; Meikle, Virginia; Bernardelli, Amelia; Abdala, Alejandro Ariel; Tarabla, Hector Dante; Romano, Maria Isabel; Cataldi, Angel Adrian (Sage Publications, 2020)
The confirmatory diagnosis of Mycobacterium bovis (M. bovis) in animal samples is carried out by culture in Stonebrink media. However, culture is very slow because of the extremely long duplication time of the bacillus and difficult because of the scarcity of bacilli in diagnostic samples. This study describes the development of a single-tube touch-down polymerase chain reaction (PCR) protocol for the detection of M. bovis using primers that target the IS6110 element. Spiked water and milk as well as routine diagnostic samples (milk and nasal swabs) from M. bovis–positive cattle were tested. This protocol allows the rapid and sensitive detection of M. bovis in bovine samples by enhancing the sensitivity of standard PCR amplification.